How are mathematicians as part of mathematics history represented in contemporary Chinese school mathematics textbooks? - Lianghuo Fan; Na Li (University of Belgrade, Teacher Education Faculty, 2020)
As part of our efforts to understand how history and culture are manifested in mathematics textbooks, we investigated particularly in this study how mathematicians are represented across three different series of contemporary school mathematics textbooks used in primary and junior secondary schools in China. The study intends to document the ways of representation of mathematicians in the three series of textbooks, compare the similarities and differences, and explore the reasons and implications of the findings concerning mathematics textbook research and development. Our findings show that each series of mathematics textbooks introduced both Chinese and non-Chinese mathematicians in a commendable way, though most of the mathematicians introduced were ancient mathematicians, and all the three series introduced mathematicians each year from Grade 2 to Grade 9. There is also a high level of consistency in the distribution of the introduction of mathematicians in the three series in terms of mathematics contents and the structures of the chapters. In comparison, we found the mathematics textbook series by the PEP presented a more balanced distribution of the introductions of mathematicians in terms of grade levels, ethnic origins and the history timeline. The explanations and implications of the findings are discussed at the end of the paper